Altruistic and egoistic prosocial behaviors among Orang Asli adolescents: its relations to attachments and prosocial value - Ma’rof, Aini Azeqa; Hamsan, Hanina Halimatusaadiah (Human Resource Management Academic Research Society, 2020)
Attachment theories postulate that attachment is crucial during adolescence and act as an important predictor to prosocial behavior. From attachment and prosocial value perspective, people develop the ability to empathize with others which is related to healthy functioning and positive helping behavior. This study therefore examine the relations between social attachments (i.e., parental, peer, school, and ethnic group attachments) and prosocial value (i.e., kindness) on the distinct type of prosocial behavioral tendencies (i.e., altruistic and egoistic prosocial behaviors). The study was conducted among the Orang Asli adolescents (N = 402) aged 14 years and 16 years from ten secondary schools in the states of Perak and Pahang and employed self-administered questionnaire. The results revealed that there were significant relationships between parental, peer and ethnic group attachments on altruistic and egoistic prosocial behavior tendencies. Significant relationship also was found on the relations between prosocial value and both prosocial behavior tendencies. However, there was no significant relationship for school attachment and both prosocial behavior tendencies. Findings from this study suggests that attachment to specific social group contribute to the distinct types of prosocial behavior tendencies, meanwhile, regardless of the types of prosocial behavior, it comes together with the kindness act. This study further discusses on the implication of attachment specifically among the Orang Asli in preserving their prosocial acts.